(untitled) (Indian Journal of Arid Horticulture, 2025)
The field experiment was conducted to study the "Effect of integrated nutrient management on yield parameters and yield of rabi onion (Allium cepa L.)" in loamy sandy soils of the Horticulture farm, S.K.N. College of Agriculture, Jobner during rabi season of 2013-14 and 2014-15. The experiment comprising of 36 treatment combinations was replicated three times, was laid out in split-plot design having three fertility levels (0,75 and 100% of recommended dose of NPKS) and three treatments of organic manures (control, FYM @ 20 tha" and poultry manure @ 5 tha") were applied in main plots. Four bio-fertilizers used sub treatments viz. (No inoculation, PSB inoculation, Azospirillum inoculation and PSB+ Azospirillum inoculation) were applied in sub plots. The results of the study envisage showed that application of inorganic fertilizers up to 75% RDF significantly increased yield parameters and yield (neck thickness, number of scales per bulb, fresh weight of bulb and yield of onion). Similarly, application of poultry manure @ 5 tha" significantly increased yield parameters and yield of onion. Application of bio-fertilizers (PSB and Azospirillum) alone or in combination significantly influenced yield parameters and yield of onion. Significant maximum values for yield was parameters and yield achieved through combined inoculation with PSB + Azospirillum. Application of 75% recommended doses of NPKS along with poultry manure @5 tha was better for realizing enhanced fresh weight of bulb and bulb yield of onion.